MODEL INKULTURASI NILAI RELIGIOUS PADA PEMBELAJARAN BIOLOGI DENGAN PENDEKATAN DISKOVERI - Mulyani, Aty; Rusdi, M.; Yelianti, Upik; Sudarmin, Sudarmin (Ibn Khaldun University, Bogor, 2023)
The objectives of research Biology matter are (1) aspects of mastery of concepts related to cognitive learning outcomes, (2) aspects of scientific work skills; and (3) aspects of religious and scientific attitudes. At this time science (Biology) learning integrated with Religious Values is still being debated regarding how what theories support it and why does it require integration? Therefore, this researcher aims to describe the inculturation learning model of Religious Values in Biology Learning with the Approach Approach because at this time religious and scientific learning has not been integrated in the sense that when teachers teach do not associate religious values. Religious values can be integrated into science learning because science and religion are closely related. While the pattern that was carried out for integration was through the process of inculturation. Inculturation has been studied by several western theologians, walisongo scholars, religious leaders in the archipelago and national education figures such as Ki Hajar Dewantara. This study developed a discovers learning model that is integrated with religious values. Through the inculturation process in its implementation, the instructional design process for the inculturation process using the ADDIE model. In the ADDIE process an analysis of the needs of students, teaching materials, learning facilities and infrastructure and needs related to the design of learning inculturation of religious values in science learning (Biology) in regular and flexible activities includes knowledge of effective teaching and learning, development that is to develop learning models inculturation of religious values in learning Biology so that it can be implemented in the learning process and evaluated. In this research conceptually, the teaching material of each sub-topic is related to the Qur'anic verses/hadith and the process can use the media of songs, poetry, religious poetry, and sholawat following the content of the subject matter of science.